2021
DOI: 10.1038/s41598-021-91416-8
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis exacerbates proteolytic imbalance and pro-fibrotic platelet dysfunction

Abstract: Multi-organ fibrosis among end stage renal disease (ESRD) patients cannot be explained by uremia alone. Despite mitigation of thrombosis during hemodialysis (HD), subsequent platelet dysfunction and tissue dysregulation are less understood. We comprehensively profiled plasma and platelets from ESRD patients before and after HD to examine HD-modulation of platelets beyond thrombotic activation. Basal plasma levels of proteolytic regulators and fibrotic factors were elevated in ESRD patients compared to healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Taken together, these data suggest that depressurization circumvents receptor signal transduction to induce exocytosis and further that this mechanism desensitizes platelets to chemical stimuli. In hemodialysis, this may contribute to bleeding disorders [ 2 ] while still exacerbating the circulation of platelet factors [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Taken together, these data suggest that depressurization circumvents receptor signal transduction to induce exocytosis and further that this mechanism desensitizes platelets to chemical stimuli. In hemodialysis, this may contribute to bleeding disorders [ 2 ] while still exacerbating the circulation of platelet factors [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early studies reported platelet morphological expansion [ 22 ], aggregation [ 23 ], and free ion flux [ 24 ] in both hyper- and hypotonic solutions with implications on blood storage. Considering the drastic shifts in osmolarity experienced in the renal medulla and procoagulant platelet phenotypes observed in representative hyperosmotic solutions [ 21 ], agonist-free platelet degranulation may contribute to worsening CKD in dialysis patients exhibiting pro-fibrotic platelet disposition [ 6 ].…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, FGF2 was found to reduce glucocorticoid-mediated bone resorption via inhibition of sclerostin signalling, reinforcing its anabolic effects on bone metabolism ( 107 ). Circulating FGF2 levels have been reported to be lower in patients with more advanced CKD ( 108 , 109 ), though its role in the development of sarcopenia in CKD is yet to be determined.…”
Section: Myokines and Bone Metabolismmentioning
confidence: 99%